The regulation strategy for releasing residual stress in ceramic-metal brazed joints. (6th January 2023) - Li, Peixin; Yan, Yaotian; Ba, Jin; Wang, Pengcheng; Wang, Haohan; Wang, Xingxing; Lin, Jinghuang; Cao, Jian; Qi, Junlei
Abstract: Ceramics and ceramic-based composites have been widely used in electronic information and communication, chemical industry, instrument manufacturing and other fields. However, due to the brittleness and processability of ceramic materials, ceramics need to be connected with metal materials to meet practical applications. Among various bonding methods, brazing is widely used for joining ceramics and metals. However, due to the difference in the properties of ceramics and metals, especially the coefficient of thermal expansion, excessive residual stresses are generated in the joint subject to deformation during the cooling process of the brazed joint. High residual stresses can seriously damage the joint properties. To relieve residual stresses, this review has summarized three residual stress relief methods: particle reinforcement, interlayer assisted control, and surface structure design. These methods can effectively relieve stress concentration in joints, improve joint plasticity, and reduce the ceramic-metal discrepancy, thus leading to the enhanced performances. Finally, the future opportunities and challenges of regulation strategy for releasing residual stress are also presented. Overall, it is expected that these stress relief strategies will provide some new understanding of the wide range of applications for ceramic-to-metal joints.